MEREKAM JEJAK SEJARAH MASJID AL-WUSTHO SURAKARTA TAHUN 1878-2013 M - Sucipto, Sucipto; Jannah, Alifa Zahrotul (Historia Islamica: Journal of Islamic History and Civilization, 2022)
Abstract This research aims at recording traces of historical heritage, Al-Wustho Mosque in Surakarta. The limitations of this study are 1878-2013 AD. The interesting thing about this is the mosque was formerly the Mangkunegaran Palace Mosque, but in its development, it became a public mosque. The Al-Wustho Mosque is one of the oldest mosques Surakarta. Therefore, the Al-Wustho Mosque has historical values ​​that are quite long, important, and interesting to study in depth. This writing applies historical research methods from Kuntowijoyo, which includes five stages: topic selection, heuristics, verification, interpretation, and historiography. The findings are that the Al-Wustho Mosque was formerly a private mosque belonging to the Mangkunegaran Palace built by Mangkunegara I in Kauman village, Pasar Legi. Then, in 1878 AD during the reign of the IV Mangkunegara, he moved the mosque building to its current position. The Al-Wusto Mosque underwent renovations during the reign of the VII Mangkunegara with the help of a Dutch-blooded architect. At the time of carrying out the renovation, the Mangkunegara VII also added buildings in the form of towers and Maligin on the right and left sides of the mosque. In its development, the Mosque switched from the Mangkunegaran Palace Mosque to a public mosque under the Ministry of Religion, after being designated as a Cultural Heritage, and now it is the responsibility of the Surakarta City government. Keywords: Al Wustho Mosque, Mangkunegaran Palace, Surakarta, History, Cultural heritage objects Abstrak Penelitian ini bertujuan untuk merekam jejak peninggalan sejarah, yang berupa Masjid Al-Wustho di Surakarta. Adapun batasan dalam penelitian ini yaitu tahun 1878-2013 M. Salah satu hal menarik dari penelitian ini ialah karena Masjid Al-Wustho dahulunya merupakan Masjid Keraton Mangkunegaran, namun dalam perkembangannya menjadi masjid umum. Masjid Al-Wustho Surakarta merupakan salah satu masjid tertua di kota Surakarta. Oleh karena itu, Masjid Al-Wustho ini memiliki nilai-nilai sejarah yang cukup panjang dan penting serta menarik untuk diteliti secara mendalam. Penulisan sejarah ini menggunakan metode penelitian sejarah dari kuntowijoyo, yang meliputi lima tahapan, yaitu: pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi. Adapun temuan di dalam penelitian sejarah ini ialah bahwa Masjid Al-Wustho Surakarta dahulunya merupakan sebuah masjid pribadi milik Kraton Mangkunegaran yang dibangun oleh Mangkunegara I di kampung Kauman, Pasar Legi. Kemudian, pada tahun 1878 M yaitu pada masa pemerintahan Mangkunegara ke-IV beliau memindahkan bangunan masjid ke posisi sekarang ini. Masjid Al-Wusto mengalami renovasi pada masa pemerintahan Mangkunegara ke-VII dengan bantuan seorang arsitek berdarah Belanda. Pada saat melakukan renovasi tersebut, Mangkunegara ke-VII juga menambahkan bangunan berupa menara dan Maligin yang berada di sisi kanan dan kiri masjid. Di dalam perkembangannya, Masjid Al-Wustho beralih dari Masjid Keraton Mangkunegaran menjadi masjid umum dibawah Departemen Keagamaan, setelah ditetapkan menjadi Cagar Budaya, dan kini menjadi tanggung jawab pemerintah Kota Surakarta. Kata kunci: Masjid Al Wustho, Keraton Mangkunegaran, Surakarta, Sejarah, Benda cagar budaya